Charter and Ordinances of the City of Trenton 185 (1875) - (:unkn) unknown (My University, 1842)
An Ordinance concerning Nuisances, 1: No merchant, storekeeper, or other person whatever, shall keep, at any one time, more than fifty pounds of gunpowder on the premises used or occupied by him, within the thickly built and inhabited parts of the city, under the penalty of fifty dollars."
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER